Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
C. x = 3, y = -6
Step-by-step explanation:
You can divide the second equation by 2. Then you have ...
x +2y = -9
This gives you a couple of choices for solution. The x-coefficients match, so subtracting one equation from the other eliminates x:
(x +2y) -(x -2y) = (-9) -(15)
4y = -24 ⇒ y = -6
Adding the two equations eliminates y:
(x -2y) +(x +2y) = (15) +(-9)
2x = 6 ⇒ x = 3
The solution is (x, y) = (3, -6).
_____
Additional comment
I find it quick and easy to use a graphing calculator to find the solution. Many graphing calculators also make it simple to solve systems of equations in matrix form. Either way, you can obtain a solution in little more than the time it takes to enter the equations (or their coefficients).
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.